Local Wisdom of Ngubat Padi: Implementation of E-Modules on Tolerance Characters - Asrial, Asrial; Syahrial, Syahrial; Kurniawan, Dwi Agus; Damayanti, Latipia (Jurnal Pendidikan Indonesia, 2022)
In elementary schools, no one has implemented learning using electronic modules based on local wisdom. This study aims to analyze the impact of using electronic modules based on local knowledge on the character of students' tolerance. This research was conducted using quantitative associative analysis, which aims to see the relationship between variables. The sample in this study was 29 students of class V, which was determined using purposive sampling. Data was collected using an instrument in the form of a questionnaire. Electronic module validation is the validation of several experts, namely linguists, material experts, media experts, and expert practitioners. The data analysis technique used in this research is descriptive statistical data analysis method and inferential statistics. The result of this research is that the correlation between the two indicators of tolerance character and student response is 0.790. The relationship between the two indicators is strong, with a probability value of 0.000 < 0.005. It was concluded that there was a relationship between the indicators of tolerance character and student responses to the application of electronic modules based on Ngubat Padi's local wisdom. In addition, students' answers to the electronic module get results in a suitable category to form students' tolerance character.